Design and simulation of an Unmanned Aerial Vehicle based on a motor glider concept. Issue 1 (1st October 2022) - Pop, S; Steopan, A; Luculescu, M C; Boer, A L; Cristea, L; Zamfira, C S
Abstract : Due to the miniaturization of optoelectronic devices, the increase in computing power, and the improvement of control systems and navigation systems, Unmanned Aerial Vehicles (UAVs) have become an indispensable tool in areas such as agriculture, industry (critical infrastructure inspection), and surveying. These systems are available in fixed-wing and rotary-wing (multiple rotors) configurations. The multiple rotor system is characterized by advantages such as vertical take-off and landing and simplicity of the structure design and control algorithm. Still, there are also disadvantages: the short flight time and very high energy consumption. Based on the requirement for a platform with high reliability and high flight range, the paper proposes a solution for fixed-wing UAVs with an extended flight time, self-launching, short landing, and optimized energy consumption. The presented solution is inspired by the model of the Romanian glider IS-28B2 produced by ICA Ghimbav, which has been redesigned and optimized to become a 1:10 scale UAV type glider. The paper presents the 3D model design, simulation, and optimal autopilot integration for this robotic aerial system.